2021
DOI: 10.1039/d1md00095k
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule-mediated induction of endoplasmic reticulum stress in cancer cells

Abstract: Endoplasmic reticulum (ER) is one of the crucial sub-cellular organelles controlling myriads of functions including protein biosynthesis, folding, misfolding and unfolding. As a result, dysregulation of these pathways in ER...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…66 Hydrazones, existing in chemotherapeutic agents and many other drugs, attached to organic molecules could be applied to drug design relevant to anticancer activities. [127][128][129] Al-Sodies et al designed and synthesized novel dicationic ILs (Di-ILs), which contained hydrazone as a spacer linking double pyridines with alkyl functionalized esters to form cations. In their experiment, the two most active Di-ILs showed 99.99% and 99.86% compromised cell ability against human lung cancer cells (A549 and H1299, respectively).…”
Section: Methotrexate ([Tbp][mtx]) L-phenylalanine Ethyl Ester Methot...mentioning
confidence: 99%
“…66 Hydrazones, existing in chemotherapeutic agents and many other drugs, attached to organic molecules could be applied to drug design relevant to anticancer activities. [127][128][129] Al-Sodies et al designed and synthesized novel dicationic ILs (Di-ILs), which contained hydrazone as a spacer linking double pyridines with alkyl functionalized esters to form cations. In their experiment, the two most active Di-ILs showed 99.99% and 99.86% compromised cell ability against human lung cancer cells (A549 and H1299, respectively).…”
Section: Methotrexate ([Tbp][mtx]) L-phenylalanine Ethyl Ester Methot...mentioning
confidence: 99%
“…Subsequently, other small molecules to induce ER stress emerged as novel strategies towards next‐generation ER targeted cancer therapy [17–25] . However, development of ER targeted novel small molecules remained in its infancy due to the lack of proper targeting moieties [26–31] …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] However, development of ER targeted novel small molecules remained in its infancy due to the lack of proper targeting moieties. [26][27][28][29][30][31] To address this, herein we have developed a library of 3-methoxy-pyrrole enamine derivatives having Dansyl or p-toluene sulfonyl (Tosyl) moieties for ER targeting (Figure 1a) through a concise three step chemical synthesis (Figure 1b). Through cell viability, confocal microscopy and gel electrophoresis studies we have identified a novel small molecule which homed into ER of the HeLa cervical cancer cells within 3 h followed by induction of ER stress leading to apoptosis to show remarkable HeLa cell killing (Figure 1d).…”
Section: Introductionmentioning
confidence: 99%